KESULITAN-KESULITAN SISWA DALAM MEMPELAJARI MATEMATIKA PADA MATERI GARIS DAN SUDUT DI SMP N 4 SINDANG - Senjaya , Aan Juhana; Sudirman; Supriyatno (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2017)
This study aims to determine the factors that cause difficulty learning mathematics in the material lines and angles at school and at home.This type of research is qualitative research. Subjects in this study were four students who have difficulty learning math class VIIB SMPN 4 Sindang. In this research, the writer used a technique Bogdan and Biklen’stechniqueto data analysis. The writer also uses triangulation observer, place, time, and theory to examine the validity of the data obtained. Based on the research results and conclusions obtained are students’difficulties in learning mathematics of the lines and anglesmaterial are (a) misunderstanding of the students toward a matter to be determined; (b) ignorance of the students to the concept of lines and angles; (c) students to the inaccuracy of writing symbols (language) mathematics; (d) the inaccuracy of students on mathematical calculations. Meanwhile, the factors that cause students learning difficulties in learning lines and angles material is divided into two factors, namely the internal and external factors. Internal factors (in students) that caused learning difficulties in learning material lines and angles are the students are no interest towards learning mathematics and how/study habits of students. Meanwhile, extern factors (outside thestudents) students' learning difficulties in learning mathematics of the material lines and angles of SMPN 4 Sindang seen through two aspects, namely environmental factors of school and family environments (home).